The Role of CDM Post-2012 - Alexander Vasa; Karsten Neuhoff (Climate Policy Initiative, 2011)
Installations covered by the European Emission Trading Scheme (EU ETS) can use credits from the Clean Development Mechanism (CDM) to cover a share of their emissions. The CDM credits are generated by low-carbon projects in developing countries that require the CDM support to become financially viable. We review the objectives that are pursued by the EU and by CDM host countries with the CDM, and assess the performance of the mechanism in reaching these objectives: Additionality Additionality is a key premise of the CDM – only projects that would not have been possible otherwise should be supported by the CDM. Studies have found, however, that between one-fifth1 and twothirds 2 of registered projects are non-additional; reasons include insufficient demonstration criteria and the ineffectiveness of Designated Operational Entities (DOE)3 in filtering non-additional projects. Assuming these estimates are valid, non-additionality could have contributed 30 to 106 million tons of CO2eq to global emissions increases through the use CDM credit in the EU ETS in 2008-2009. Efficient use of EU mitigation funds CDM may not be a cost-effective mechanism for mitigation. For example, yearly costs for abating all developing HFC-23 would cost about exteuro26 million, but through the CDM, Annex I buyers pay between exteuro250 and exteuro750 million in total.4 Sustainable Development The definition of sustainable development is controversial and there is no agreement on how it should be measured. Within this context, it is difficult to determine whether CDM aids sustainable development or not. Some CDM experts go so far as to suggest – using their sustainable development criteria - that the additionality requirements of CDM actually reduce the number of sustainable projects available for CDM investment. Low-carbon development – In developing countries In developing countries, the authors find that the CDM has not facilitated technology transfer, does not support a shift to low-carbon technologies, can discourage the development of domestic lowcarbon policies such as Nationally Appropriate Mitigation Actions (NAMAs), does not achieve sustainable development criteria, and, in fact, can support carbon-intensive activities. Low-carbon development – in Europe Overall, the CDM negatively impacts EU ETS abatement. This study shows that with an EU ETS target of 20%, the CDM decreases the required GHG emissions reductions from 13.8% to 7.5% by 2020 (relative to 2005).5 The right to use CDM has been extended to the period 2013-2020. As a result, averaged over the period 2008-2020, EU ETS emissions can exceed the EU ETS cap by 7.3%. 1 Michaelowa & Purohit, 2007 2 Wara and Victor, 2008 3 In the CDM context, the term DOE stands for validators of CDM project proposals. In the US, the term DOE stands for Department of Energy. 4 Wara, 2008 5 EU Community Independent Transaction Log (CITL) data. See section 2.1 and Annex 1 The Role of CDM Post-2012 January 2011 Carbon Pricing for Low-Carbon Investment Project 4 Thus the degree of abatement undertaken in Europe is heavily influenced by the use of CDM credits. With a 30% target, the effects are even more pronounced, with emission reductions delivered domestically of 23.9% without CDM use to 12.6% with CDM use.6 Even without the use of CDM, the current 20% emissions trajectory results in emissions abatement of 51% below 1990 levels by 2050, which falls well short of the commitment of 80-95%, formulated by the EU and its Member States at the EU Summit in October 2009.7 Future volumes of CER inflows are determined by various factors inherent in the choice of project and technology, and are also determined by political decisions made at the UN, EU, and project host country level. This makes the volumes of CERs generated difficult to predict, despite careful monitoring by market participants and analysts of international carbon market developments. CDM in the case of a 30% EU emissions reduction target If the EU moves to a 30% target, the Directive currently envisages that half of the additional emissions reductions could be covered with CDM credits. Policy makers may consider, whether the performance of the CDM mechanism to date justifies such an expansion, or the focus should be shifted on alternative mechanisms for international climate cooperation. Should the increased use of CDM still proceed, this might trigger a discussion about who receives the right to use the CDM credits and can capture the rents from the price spread between EU allowances and CERs. This could repeat the lengthy debate between industry and the European Commission on the definition of benchmarks for free allowance allocation. This paper explores and discusses different options for how market-based mechanisms could be used instead, to allocate the right for the use of CER credits.
Keywords: Q48; Q54; K23; 330; Carbon Pricing; Power; Climate Policy; Investment Support; Clean development mechanism; Electric Utility Industry; Climate Policy; Investment policy